(untitled) (Journal of Computational Mathematics, 2004)
This paper deals with H-stability of Runge-Kutta methods with variable stepsize for the system of pantograph equations. It is shown that both Runge-Kutta methods with nonsingular matrix coefficient A and stiffly accurate Runge-Kutta methods are H-stable if and only if the modulus of stability function at infinity is less than 1.